(untitled) (REVISTA NERA, 2012)
This paper investigates processes of place-making and community formation following agrarian reform resettlement in Brazil. Based on case studies conducted between 2002 and 2004 in several settlements organized by the Movimento dos Trabalhadores Rurais Sem Terra (MST) in the Brazilian state of Mato Grosso, I argue that resettlement through agrarian reform in Brazil is a process of intentional community-building through resettlement and emplacement. Ethnographic data from one settlement, Antonio Conselheiro, shows that land recipients passed through a series of physical movements [displacement, occupation, encampment, settlement] that shape the production of locality, or what I refer to here as emplacement. I discuss key social processes that contribute to emplacement: the transition from individual to imagined community, from imagined community to collectivity, and from collectivity to place-based community.